Climate Resilient Maize Production in Chepang and Non-Chepang Farming Communities of Chitwan, Nepal - Sharma, Pratiksha; Kattel, Rishi Ram; Subedi, Ananta Prakash (International Journal of Applied Sciences and Biotechnology, 2020)
This research was conducted to assess farmer’s adaptation strategies of climate change in maize cultivation among Chepang and Non-Chepang communities in Chitwan. Pre-tested questioner, direct observation and secondary data were collected and used. Data analysis was done by using descriptive statistics, time series regression, Logit and seemingly unrelated regression model. Productivity of study area was found to be positively affected by total rainfall whereas negatively affected by average temperature. Majority of respondents (86.7%) were found to adopt any one of the climate change related adaptation strategies on maize cultivation. Among various adaptation strategies, mix cropping (66.3%) was found major in the study areas. Head of household, knowledge about climate change and economically active members in the family were positive determinant on adoption of climate change adaptation strategies.SUR model showed that education of household head, economically active member in the household, an involvement in extension/ training and maize production were major positively significant explanatory variables whereas age, gender of household head and involvement in an organization were major negatively significant explanatory variables in farmer’s decision for adaptation of different climate change combating strategies. The study concluded that farmers of Chitwan perceived change in climate with negative effect on their maize cultivation practices. In comparison to Non-Chepang, Chepang farmers had less knowledge and adaptation practices. More focus from government and Nongovernment sector through proper policy implementation and technology intervention is needed to support this backward community. Int. J. Appl. Sci. Biotechnol. Vol 8(1): 71-77